An Analysis of Idiomatic Expressions in The Animated Series “Gravity Falls” Season 1 Episode 1 & 2 (2012) - Setiawan, Rahmat Agung; Modjanggo, Vivin Krismawanti; Toedje, Charles Setiawan (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research investigates the types and frequency of idiomatic expressions used in the animated series Gravity Falls (2012), created by Robert Hirsch. Employing a descriptive qualitative approach, the researchers analysed transcripts from two selected episodes: Episode 1, Tourist Trap, and Episode 2, The Legend of the Gobblewonker. The analysis was guided by the typology of idioms proposed by O'Dell and McCarthy (2010), which categorizes idioms into six distinct types. The findings indicate the presence of three types of idiomatic expressions across the two episodes: clichés and fixed statements (10 instances), binomials (1 instance), and euphemisms (2 instances). Among these, clichés and fixed statements emerged as the most dominant category. Specifically, seven instances of this type were found in the first episode, while the remaining three occurred in the second.